A Cryopreservatlon method of Sclzaphyllurn commune local strains - Mohd Kamal, Irnada Syuhaidah; Mohd Nor Rashid, Noraswati; Mel, Maizirwan (2011)
Schizophyllan commune fsolates were collected from rubber plantations in Selangor and Perak area in Malaysia. Spawns were prepared using three different grains (wheat, corn and paddy). The grains were incubated for 7 days at room temperature. After the grains were fully covered with myceHa, they were place into a cryo-vial with three different. treatments, 10% glycerol, sterile distilled water and no cryoprotectants. AU of the treatments were frozen in liquid nitrogen for 7 days followed by thawing (cooling) at 30°C for 30 min. The grains were inoculated onto PDA agar to observe the viability (rate of survival) of the seeds. The radius of each grain with different treatments was measured. Results showed that all treatments showed 100% viability aft.er 48 hours and wheat wit.h no cryoprotectants showed the highest growth rate. This indicated that the grains have mycelial protective properties. In this study, a cryopreservation process was simplified as opposed to the conventional method in which 10% glycerol was used as the cryoprotectant. This study promotes an alternative method for cryopreservalion which is more economical as no cryoprotectants were required.